General Features Of The System Of Interpersonal Relationships In The Family - Shomurodova Mohichehra Jahongirovna; Oymatova Dilorom Ro'zimurotovna (Euro Asian Journal Publishing, 2025)
This article examines the general characteristics of the system of interpersonal relationships in the family. The relationships between individuals within the family – parents, children, siblings and other relatives – are analyzed from a psychological and social perspective. Factors such as trust, respect, affection, responsibility, cooperation and communication play an important role in this system. It is also emphasized that a healthy family environment is of great importance in the process of personal development and social adaptation. The topic also covers roles in the family, their functions and mechanisms for managing conflicts
Keywords: family; interpersonal relationships; social system; communication